Utilization of E-Business to Enhance Efficiency and Innovation in the Micro, Small, and Medium Enterprises (MSMEs) Sector - Takwa, Muhammad; Kasyati, Kasyati; Supriadi, Drajat; Prabowo, Hanif Agung; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The advancement of e-business has significantly transformed the operational landscape for Micro, Small, and Medium Enterprises (MSMEs). This literature review aims to explore how the utilization of e-business technologies contributes to enhancing efficiency and fostering innovation within the MSME sector. By analyzing scholarly articles and industry reports published between 2015 and 2024, this review identifies the key drivers, challenges, and impacts of e-business adoption. Findings suggest that e-business adoption improves process efficiency, reduces operational costs, facilitates market expansion, and drives innovative business models. However, barriers such as limited digital literacy, inadequate infrastructure, and cybersecurity threats persist. This review concludes with strategic recommendations for MSMEs and policymakers to support digital transformation.